2008
DOI: 10.1074/jbc.m800019200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Human Enzyme RDH10 Defines the Characteristics of a Physiologically Relevant Retinol Dehydrogenase

Abstract: Human retinol dehydrogenase 10 (RDH10) was implicated in the oxidation of all-trans-retinol for biosynthesis of all-transretinoic acid, however, initial assays suggested that RDH10 prefers NADP ؉ as a cofactor, undermining its role as an oxidative enzyme. Here, we present evidence that RDH10 is, in fact, a strictly NAD ؉ -dependent enzyme with multisubstrate specificity that recognizes cis-retinols as well as all-trans-retinol as substrates. RDH10 has a relatively high apparent K m value for NAD ؉ (ϳ100 M) but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 48 publications
8
78
1
Order By: Relevance
“…Biochemical analysis carried out in our laboratory revealed that human ortholog of RDH10 (SDR16C4) recognizes not only all-trans-retinol but also 11-cis and 9-cis retinols as substrates and strongly prefers NAD + as a cofactor, in agreement with the structural determinants of SDR cofactor specifi city ( 47 ). This fi nding contradicted the previous report that human RDH10 has a signifi cant activity with NADP + ( 43 ).…”
Section: Biosynthesis Of Atra From Retinolcontrasting
confidence: 67%
See 1 more Smart Citation
“…Biochemical analysis carried out in our laboratory revealed that human ortholog of RDH10 (SDR16C4) recognizes not only all-trans-retinol but also 11-cis and 9-cis retinols as substrates and strongly prefers NAD + as a cofactor, in agreement with the structural determinants of SDR cofactor specifi city ( 47 ). This fi nding contradicted the previous report that human RDH10 has a signifi cant activity with NADP + ( 43 ).…”
Section: Biosynthesis Of Atra From Retinolcontrasting
confidence: 67%
“…In comparison with SDR9C all-trans -retinol/sterol dehydrogenases, human RDH10 is not active toward 3 ␣ -hydroxysteroids, and it exhibits a much higher affi nity for all-trans -retinol ( ‫ف‬ 28-fold) than does either RoDH4 or RL-HSD ( 47 ). When overexpressed in a model of human organotypic skin raft culture, only RDH10 [not RoDH4, RL-HSD, or DHRS9 (RDHL)] induces a phenotype consistent with overproduction of atRA, which is characterized by an increased proliferation and reduced differentiation of keratinocytes ( 48 ).…”
Section: Biosynthesis Of Atra From Retinolmentioning
confidence: 98%
“…RDH10 was found to be a strictly NAD ϩ -specific enzyme with dual specificity for trans-and cis-retinol, consistent with earlier findings (18). In cells, the concentration of NAD ϩ is higher than that of NADP ϩ , which could cause Rdh10 to evolve its strict specificity toward NAD ϩ (29,30).…”
Section: Rdh10 Has 11-cis-retinolsupporting
confidence: 89%
“…Wu et al (13) reported that RDH10 is an efficient all-trans-RDH with NADP ϩ as its preferred cofactor. However, Belyaeva et al (18) demonstrated that RDH10 is an efficient 11-cis-RDH with NAD ϩ as its preferred cofactor. The in vivo role of RDH10 in the visual cycle has not been reported.…”
Section: Rdh11mentioning
confidence: 99%
See 1 more Smart Citation